The Health Sector - From Desideratum to Real Reform - Mihoreanu, Larisa (Journal of Economic Development, Environment and People, 2019)
The paper states the necessity to implement a new model of management in the health sector, based on a new concept, of synergetic satisfaction having an institutional relation between patient and medical entity in its centre. The present doctoral research finds its roots in the interdisciplinary approach linked to Health industry and market, as profitable businesses. The purpose encounters the anchor into a new concept, of synergetic satisfaction having the patient in its centre. The measurement centre resides in the societal performances’ rules linked to the real needs of a health status afterthought. Several constituents of the classical healthcare principles receive, exquisitely, shaped clarifications under the state, public and private health of public recognition. As the principles of humanism depict the governments’ obligation to guarantee their citizens fundamental rights to access health services, the international dimension of activities seed new designed health objectives. Hence the research maps a new model sustaining that the health management systems, differently recognized, can assume regular nudgers to better drive the understanding of the reality, close to financial interests and realistic resources. The implementation of the innovative and realistic reform would diminish the national burden, make people embrace the responsibility of active citizenship letting them to get involved in any process that protect the right development of a country and its citizens, far from partisan interests, only for their own future and comfort in life.